Avaliação da correlação entre ansiedade-traço e ansiedade-estado em indivíduos submetidos a situações ansiogênicas - Leal, Pollyana Caldeira (2013)
Objective: In studying anxiety, the concepts of state anxiety (reactive) and trait anxiety (personality trait) are distinguished, while it is believed that the higher the trait anxiety, the higher the state anxiety in different situations of threat. Thus, the aim of this study was to investigate the correlation between trait anxiety and state anxiety in volunteers exposed to two distinct anxiogenic situations: an interpersonal threat (Video-Monitored Stroop Test VMST; n=30) and a physical threat (Third Molar extraction TME; n=20). Method: Healthy male subjects had their physiological (heart rate HR; gastrocnemius electromyography - GEM) and psychological parameters (Trait-State Anxiety Inventory STAI; Self-evaluation of tension level - STL; Social Phobia Inventory - SPIN, Hospital Anxiety and Depression Scale - HAD; Dental Anxiety Scale - DAS) evaluated in three different situations: Before, During and After the VMST or the TME. A correlational study was conducted. Scores of STAI-T, DAS, HAD and SPIN were confronted with scores of STAI-E, STL, HR and GEM in each experimental situation (Before, During and After). A level of significance of 5% was considered. Results: In the VMST, STAI-T, HAD and SPIN correlated with STAI-S in all test situations and of STL in most situations. In relation to the TME, STAI-T and HAD were not correlated neither with the STAI-E nor with the STL in any experimental situation. DAS correlated with STAI-E and the STL before and during the test. In both VMST and TME, correlations of psychological with physiological measures were not found in any of the experimental situations. Conclusion: The level of physiological alterations may not reflect the level of anxiety and the anxious trait should be considered as a multidimensional concept, once trait anxiety modulated anxious responses to interpersonal threat, but not to physical threat.